# Misc 3 - Chapter 9 Class 11 Sequences and Series (Term 1)

Last updated at May 29, 2018 by Teachoo

Miscellaneous

Misc 1
Deleted for CBSE Board 2023 Exams

Misc 2 Deleted for CBSE Board 2023 Exams

Misc 3 Important Deleted for CBSE Board 2023 Exams You are here

Misc 4 Deleted for CBSE Board 2023 Exams

Misc 5 Deleted for CBSE Board 2023 Exams

Misc 6 Important Deleted for CBSE Board 2023 Exams

Misc 7 Important

Misc 8

Misc 9

Misc 10 Important

Misc 11

Misc 12

Misc 13

Misc 14 Important

Misc 15 Deleted for CBSE Board 2023 Exams

Misc 16 Important Deleted for CBSE Board 2023 Exams

Misc 17

Misc 18

Misc 19 Important

Misc 20

Misc 21 (i) Important Deleted for CBSE Board 2023 Exams

Misc 21 (ii) Deleted for CBSE Board 2023 Exams

Misc 22 Important Deleted for CBSE Board 2023 Exams

Misc 23 Important Deleted for CBSE Board 2023 Exams

Misc 24 Deleted for CBSE Board 2023 Exams

Misc 25 Important Deleted for CBSE Board 2023 Exams

Misc 26 Deleted for CBSE Board 2023 Exams

Misc 27 Deleted for CBSE Board 2023 Exams

Misc 28 Important Deleted for CBSE Board 2023 Exams

Misc 29 Important

Misc 30 Deleted for CBSE Board 2023 Exams

Misc 31 Important

Misc 32 Important Deleted for CBSE Board 2023 Exams

Last updated at May 29, 2018 by Teachoo

Misc 3 Let the sum of n, 2n, 3n terms of an A.P. be S1, S2 and S3, respectively . Show that S3 = 3 (S2– S1) We know that Sum of n terms = n/2 [2a + (n – 1)d] i.e. Sn = n/2 [2a + (n – 1)d] where a is the first term & d is the common difference of the A.P. It is given that Sum of n terms = S1 i.e. n/2 [2a+(n – 1)d] = S1 Also, Sum of 2n terms = S2 i.e. 2n/2 [2a + (2n – 1)d] = S2 And Sum of 3n terms = S3 i.e. 3n/2 [2a + (3n – 1)d] = S3 We want to show S3 = 3(S2 – S1) Taking R.H.S 3(S2 – S1) = 3[2n/2 " [2a + (2n" −"1)d]" −n/2 " [2a + (n" −"1)d]" ] = 3 (n/2)["2[2a + (2n" −"1)d]" −"[2a + (n" −"1)d]" ] = 3n/2 ["2(2a) + 2(2n" −"1)d" −"2a" −"(n" −"1)d" ] = 3n/2 ["4a + (4n" −"2)d" −"2a" −"(n" −"1)d" ] = 3n/2 ["4a + 4nd" −"2d" −"2a" −"nd + d" ] = 3n/2 ["4a" −"2a + 4nd" −"nd" −"2d + d" ] = 3n/2 ["2a + 3nd" −"d" ] = 3n/2 ["2a + (3n – 1)d" ] From (3), S3 = 3𝑛/2 [2a + (3n – 1)d = S3 = L.H.S Hence, R.H.S = L.H.S Hence proved